A full composite hollow dot-matrix-honeycomb hybrid sandwich structure and a preparation method thereof

CN117087246BActive Publication Date: 2026-10-20NORTHEAST DIANLI UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311060033.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2026-10-20
Estimated Expiration
2043-08-22

AI Technical Summary

Technical Problem

[0004]本发明的目的在于,提出一种全复合的中空点阵-蜂窝混杂夹芯结构及制备方法,旨在解决现有金属结构的蜂窝夹芯结构强度高但是重量大,在实际工程中受重量影响造成使用限制

Benefits of technology

[0019]1、本发明蜂窝芯层由蜂窝嵌锁组成片镶嵌于蜂窝模具中,组成点阵加强玻璃纤维蜂窝增强体,然后浇铸碳树脂基碳纳米管溶液得到,中空点阵-蜂窝混杂夹芯结构,蜂窝芯上下均匀,弯折角度也较为均匀,能够使成型后的蜂窝板具有比较平均的力学性能,能够做到在同一方向上各向同性,制备出的蜂窝芯层三明治纤维增强板具有重量轻、密度小、强度高以及刚性好等优点,并且具有优异的抗冲击减振特性,在隔音,隔热方面也具有良好的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117087246B_ABST
    Figure CN117087246B_ABST
Patent Text Reader

Abstract

The application discloses a full-composite hollow dot array-honeycomb hybrid sandwich structure and a preparation method, and belongs to the technical field of full-composite plates. The sandwich structure comprises an upper panel, a lower panel and a honeycomb core layer. The honeycomb core layer is composed of a honeycomb tessellation which is inlaid in a honeycomb mold, a dot array reinforcing fiber honeycomb reinforcing body is formed, and then a resin-based carbon nanotube solution is cast to obtain the honeycomb core layer. The upper panel and the lower panel are placed in parallel, and the honeycomb core layer is placed between the upper panel and the lower panel to form the full-composite hollow dot array-honeycomb hybrid sandwich structure. The sandwich structure prepared by the application is a full-composite material, the honeycomb core is uniform in up and down, and the bending angle is also relatively uniform, so that the formed honeycomb plate has relatively average mechanical properties and can be isotropic in the same direction. The prepared honeycomb core layer sandwich fiber reinforced plate has the advantages of light weight, small density, good strength and excellent impact performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fully composite panel technology, specifically relating to a fully composite hollow lattice-honeycomb hybrid sandwich structure and its preparation method. Background Technology

[0002] Composite honeycomb sandwich panels possess excellent weight reduction, sound insulation, and heat insulation properties, as well as better stability and stiffness, thus they are widely used in aerospace, shipbuilding, and other fields. Their main advantage lies in their greater structural stiffness for the same weight, resulting in better impact resistance and vibration damping performance. In practical engineering, a large number of this type of sandwich structure components exist, and their operating conditions are becoming increasingly demanding, thus requiring the honeycomb core layer sandwich fiber reinforced panels to possess good mechanical properties.

[0003] Most existing honeycomb sandwich panels are made of metal materials. For example, Paik Paik JK, Thayamballi AK, Kim G S. The strength characteristics of aluminum honeycomb sandwich panels[J]. Thin-walled structures, 1999, 35(3): 205-231; Hazizan Hazizan MA, Cantwell WJ. The low velocity impact response of an aluminum honeycomb sandwich structure[J]. Composites Part B: Engineering, 2003, 34(8): 679-687. et al. have studied aluminum honeycomb sandwich structures and believe that aluminum sandwich structures are a promising structural design. However, due to the large weight of metal honeycomb composite panels, hollow designs are usually adopted. Although this design can reduce the weight of the structure to a certain extent, it will also affect the strength of the structure. Existing technologies also use perforation on the panels to reduce the weight of the panels, but this method is heavy and also affects the strength, which limits its use in practical engineering. Therefore, the design consideration of using composite materials to prepare fully composite honeycomb sandwich panels is of great significance, as it can reduce the weight of the structure while also having good strength and excellent impact performance. Summary of the Invention

[0004] The purpose of this invention is to propose a fully composite hollow lattice-honeycomb hybrid sandwich structure and its preparation method, aiming to solve the problem that existing metal honeycomb sandwich structures have high strength but are heavy, limiting their use in practical engineering. The sandwich structure prepared by this invention is a fully composite material. The honeycomb core layer consists of honeycomb interlocking sheets embedded in a honeycomb mold to form a lattice-reinforced glass fiber honeycomb reinforcement, which is then obtained by casting a carbon resin-based carbon nanotube solution. The hollow lattice-honeycomb hybrid sandwich structure has advantages such as high strength and light weight, and can be applied in aerospace, shipbuilding, and marine fields.

[0005] One objective of this invention is to provide a fully composite hollow lattice-honeycomb hybrid sandwich structure. The sandwich structure includes an upper panel, a lower panel, and a honeycomb core layer. The honeycomb core layer is formed by embedding honeycomb interlocking sheets into a honeycomb mold to form a lattice-reinforced fiber honeycomb reinforcement, which is then obtained by casting a resin-based carbon nanotube solution. The upper and lower panels are placed in parallel, and the honeycomb core layer is placed between the upper and lower panels to form a fully composite hollow lattice-honeycomb hybrid sandwich structure.

[0006] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the honeycomb interlocking assembly includes multiple interlocking pieces, all of which are connected in a bent manner to form the honeycomb interlocking assembly, and the included angle of the bend is 120°.

[0007] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the bending points of adjacent locking pieces are provided with locking grooves, and the locking pieces are vertically locked and inserted into the locking grooves to form a honeycomb shape embedded in the honeycomb mold.

[0008] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the locking piece is composed of 3-8 layers of fiber cloth, which are bonded together by an adhesive to form a prepreg. The prepreg is cut into pieces and locking grooves are opened to form the locking piece. The locking piece has a height of 2mm and a length of 105-150mm. The adhesive is IN2 flow-conducting resin.

[0009] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the preparation method of the resin-based carbon nanotube solution includes the following steps:

[0010] The epoxy flow-conducting resin and emulsifier are mixed evenly and stirred in a water bath until all air bubbles are eliminated. Then, carbon nanotubes and glass fibers are added in sequence and stirred evenly. After adding the curing agent and mixing evenly, the mixture is heated and stirred in a water bath and vacuum degassing is performed to obtain a resin-based carbon nanotube solution.

[0011] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the amount of emulsifier is 9-11 wt% of the total amount of epoxy flow-conducting resin, the epoxy flow-conducting resin is IN2 epoxy flow-conducting resin, the emulsifier is TX-10 emulsifier, and the water bath temperature is 40°C.

[0012] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the amount of carbon nanotubes is 0.4-0.6 wt% of the total amount of epoxy conductive resin, the amount of glass fiber is 0.4-0.6 wt% of the total amount of epoxy conductive resin, and the glass fiber is CR17 glass fiber.

[0013] Preferably, in the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, the amount of curing agent is 25-35 wt% of the total amount of epoxy superplastic resin, the curing agent is AT 30 curing agent, the vacuum degassing treatment temperature is 80℃, and the vacuum degree is 10. -4 Pa.

[0014] One objective of this invention is to provide a method for preparing the above-mentioned fully composite hollow lattice-honeycomb hybrid sandwich structure, comprising the following steps:

[0015] S1. A prepreg is made by bonding multiple layers of fiber cloth with resin. The prepreg is cut into pieces and interlocking grooves are opened to form interlocking pieces. All the interlocking pieces are connected in a bent manner to form a honeycomb interlocking assembly piece. The included angle of the bend is 120°. The interlocking pieces are interlocked in a vertical manner through the interlocking grooves to form a honeycomb shape embedded in the honeycomb mold.

[0016] S2. Pour the carbon resin-based carbon nanotube solution into the honeycomb mold. After filling the honeycomb mold, let it stand for 15-24 hours and then demold to obtain the honeycomb core layer. Adhere the upper panel and the lower panel to the upper and lower surfaces of the honeycomb core layer with adhesive film to obtain a fully composite hollow lattice-honeycomb hybrid sandwich structure.

[0017] Preferably, the upper panel and the lower panel are fiber composite boards.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The honeycomb core layer of this invention is formed by embedding honeycomb interlocking sheets into a honeycomb mold to form a lattice-reinforced glass fiber honeycomb reinforcement, and then casting a carbon resin-based carbon nanotube solution to obtain a hollow lattice-honeycomb hybrid sandwich structure. The honeycomb core is uniform from top to bottom and the bending angle is also relatively uniform, which enables the formed honeycomb panel to have relatively uniform mechanical properties and isotropic in the same direction. The prepared honeycomb core layer sandwich fiber reinforced board has the advantages of light weight, low density, high strength and good rigidity, and has excellent impact resistance and vibration reduction characteristics. It also has good performance in sound insulation and heat insulation.

[0020] 2. The honeycomb hybrid sandwich core preparation process of this invention is simple and can greatly reduce the cost of making honeycomb core layer sandwich fiber reinforced board. There are no safety hazards in the preparation process, which is of great benefit to the safety of the production personnel. The honeycomb core layer sandwich fiber reinforced board has the characteristics of being lightweight and having excellent sound insulation and vibration isolation performance. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of a transverse honeycomb interlocking assembly formed by connecting seven interlocking pieces according to the present invention;

[0022] Figure 2 This is a schematic diagram of a transverse honeycomb interlocking assembly formed by connecting nine interlocking pieces according to the present invention;

[0023] Figure 3 This is a schematic diagram of a transverse honeycomb interlocking assembly formed by connecting 10 interlocking pieces according to the present invention;

[0024] Figure 4 This is a schematic diagram of a vertical honeycomb interlocking assembly formed by connecting seven interlocking pieces according to the present invention;

[0025] Figure 5 This is a schematic diagram of a vertical honeycomb interlocking assembly formed by connecting nine interlocking pieces according to the present invention;

[0026] Figure 6 This is a schematic diagram of a vertical honeycomb interlocking assembly formed by connecting 10 interlocking pieces according to the present invention;

[0027] Figure 7 This is a schematic diagram of the honeycomb interlocking components of the present invention being inlaid into a honeycomb shape;

[0028] Figure 8 This is a schematic diagram of the honeycomb interlocking components of the present invention being inlaid in a honeycomb shape within a honeycomb mold.

[0029] Figure 9 This is a schematic diagram of carbon resin-based carbon nanotubes cast using a honeycomb mold according to the present invention.

[0030] Figure 10 This is an impact performance diagram of the hollow lattice-honeycomb hybrid sandwich structure of Embodiment 1 of the present invention;

[0031] Figure 11 This is an impact performance diagram of the hollow lattice-honeycomb hybrid sandwich structure in Embodiment 1 of the present invention when the impact position is changed. Detailed Implementation

[0032] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. The described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The fiber composite board was purchased from Yixing Junchao Carbon Fiber Products Co., Ltd., and the sample name was T300 / epoxy composite.

[0033] Example 1

[0034] A fully composite hollow lattice-honeycomb hybrid sandwich structure is disclosed. The sandwich structure includes an upper panel, a lower panel, and a honeycomb core layer. The honeycomb core layer is formed by embedding honeycomb interlocking sheets into a honeycomb mold to form a lattice-reinforced fiber honeycomb reinforcement, which is then obtained by casting a resin-based carbon nanotube solution. The upper and lower panels are placed in parallel, and the honeycomb core layer is placed between the upper and lower panels to form a fully composite hollow lattice-honeycomb hybrid sandwich structure. The upper and lower panels are fiber composite boards.

[0035] like Figure 1-6 As shown, the honeycomb interlocking assembly comprises multiple interlocking pieces, all of which are connected in a bent manner to form the honeycomb interlocking assembly, with the included angle of the bend being 120°. Interlocking grooves are formed at the bends of adjacent interlocking pieces, and the interlocking pieces are vertically interlocked through these grooves to form a honeycomb structure (e.g., ...). Figure 7 (As shown) is embedded in the honeycomb mold.

[0036] The locking plate is composed of 5 layers of fiber cloth, which are bonded together by an adhesive and IN2 guiding resin to form a prepreg. The prepreg is cut into pieces and locking grooves are made to form the locking plate. The locking plate has a height of 2mm and a length of 105mm.

[0037] The method for preparing the resin-based carbon nanotube solution includes the following steps:

[0038] IN2 epoxy flow-conducting resin and TX-10 emulsifier were placed in a beaker and mixed evenly. The amount of emulsifier was 10 wt% of the total amount of epoxy flow-conducting resin. The beaker was placed in a 40°C water bath and stirred at 500 r / min for 30 min until all bubbles were eliminated to obtain the resin matrix.

[0039] Weigh out carbon nanotubes and CR17 glass fibers, with the amount of carbon nanotubes being 0.5 wt% of the total epoxy resin and the amount of CR17 glass fibers being 0.5 wt% of the total epoxy resin. Add these two reinforcements to the resin matrix solution being stirred and continue stirring at 500 r / min for 30 min until the reinforcements and resin matrix are evenly mixed. Then add AT 30 curing agent, with the amount of AT 30 curing agent being 30 wt% of the total epoxy resin. Continue stirring the evenly mixed glass fiber / carbon nanotube reinforced resin matrix solution in a 40℃ water bath for 5 min to ensure the curing agent and resin matrix solution are fully mixed. Finally, place the fully mixed glass fiber / carbon nanotube reinforced resin matrix solution in a preheated vacuum drying oven for vacuum degassing treatment. The drying oven temperature is 80℃ and the vacuum degree is 10. -4 Pa yielded a resin-based carbon nanotube solution.

[0040] The above-mentioned method for preparing a fully composite hollow lattice-honeycomb hybrid sandwich structure includes the following steps:

[0041] S1. A prepreg is formed by bonding multiple layers of fiber cloth with resin. The prepreg is cut into sheets and interlocking grooves are cut to form interlocking pieces. All the interlocking pieces are connected in a bent manner to form a honeycomb interlocking assembly. The included angle of the bend is 120°. Multiple interlocking pieces are connected in a bent manner to form transverse sections of different lengths (e.g., ...). Figure 1-3 (as shown) and vertical honeycomb (as shown) Figure 4-6 As shown, the interlocking components have interlocking grooves at the bends of adjacent interlocking pieces. The interlocking grooves on the transverse honeycomb interlocking components are located below the length of the interlocking pieces, while the interlocking grooves on the vertical honeycomb interlocking components are located above the length of the interlocking pieces. Figure 7 As shown, horizontal and vertical honeycomb interlocking components of different lengths are interlocked vertically to form a honeycomb pattern embedded in the honeycomb mold, as follows. Figure 8 As shown, the honeycomb mold is a hexagonal honeycomb silicone mold;

[0042] S2, such as Figure 9 As shown, a carbon resin-based carbon nanotube solution is slowly poured into the gaps of a honeycomb mold. After filling the gaps, the mold is left to stand for 24 hours before demolding to obtain the honeycomb core layer. The adhesive film is heated at 180°C for 30 minutes in a hot box and then covered on the top and bottom panels respectively. The adhesive film is then used to bond the honeycomb core layer to the top and bottom panels to obtain a fully composite hollow lattice-honeycomb hybrid sandwich structure.

[0043] Example 2

[0044] A fully composite hollow lattice-honeycomb hybrid sandwich structure is disclosed. The sandwich structure includes an upper panel, a lower panel, and a honeycomb core layer. The honeycomb core layer is formed by embedding honeycomb interlocking sheets into a honeycomb mold to form a lattice-reinforced fiber honeycomb reinforcement, which is then obtained by casting a resin-based carbon nanotube solution. The upper and lower panels are placed in parallel, and the honeycomb core layer is placed between the upper and lower panels to form a fully composite hollow lattice-honeycomb hybrid sandwich structure. The upper and lower panels are fiber composite boards.

[0045] The honeycomb interlocking assembly comprises multiple interlocking pieces, all of which are connected in a bent manner to form the honeycomb interlocking assembly, with the included angle of the bend being 120°. Interlocking grooves are formed at the bends of adjacent interlocking pieces, and the interlocking pieces are vertically interlocked through these grooves to form a honeycomb shape embedded in the honeycomb mold.

[0046] The locking plate is composed of 5 layers of fiber cloth, which are bonded together by an adhesive and IN2 guiding resin to form a prepreg. The prepreg is cut into pieces and locking grooves are made to form the locking plate. The locking plate has a height of 2mm and a length of 135mm.

[0047] The method for preparing the resin-based carbon nanotube solution includes the following steps:

[0048] IN2 epoxy flow-conducting resin and TX-10 emulsifier were placed in a beaker and mixed evenly. The amount of emulsifier was 9 wt% of the total amount of epoxy flow-conducting resin. The beaker was placed in a 40°C water bath and stirred at 500 r / min for 30 min until the bubbles were completely eliminated to obtain the resin matrix.

[0049] Weigh out carbon nanotubes and CR17 glass fibers, with the amount of carbon nanotubes being 0.4 wt% of the total epoxy resin and the amount of CR17 glass fibers being 0.4 wt% of the total epoxy resin. Add these two reinforcements to the resin matrix solution being stirred and continue stirring at 500 rpm for 30 minutes until the reinforcements and resin matrix are evenly mixed. Then add AT 30 curing agent, with the amount of AT 30 curing agent being 25 wt% of the total epoxy resin. Continue stirring the evenly mixed glass fiber / carbon nanotube reinforced resin matrix solution in a 40°C water bath for 5 minutes to ensure the curing agent and resin matrix solution are fully mixed. Finally, place the fully mixed glass fiber / carbon nanotube reinforced resin matrix solution in a preheated vacuum drying oven for vacuum degassing treatment. The oven temperature is 80°C and the vacuum degree is 10. -4Pa yields a resin-based carbon nanotube solution. This solution possesses extremely high specific surface area and specific strength, achieving a balance between material strength and weight. Carbon nanotubes exhibit excellent mechanical properties, with a tensile strength reaching 50-200 GPa, which is 100 times that of steel, yet its density is only 1 / 6 that of steel. Using carbon nanotubes as a reinforcing agent in the resin solution can improve its stiffness and impart a certain degree of toughness without significantly increasing its mass.

[0050] The above-mentioned method for preparing a fully composite hollow lattice-honeycomb hybrid sandwich structure includes the following steps:

[0051] S1. A prepreg is formed by bonding multiple layers of fiber cloth with resin. This prepreg is then cut into sheets and interlocking grooves are cut into them to form interlocking pieces. All the interlocking pieces are connected in a bent manner to form a honeycomb interlocking assembly. The included angle of the bend is 120°. Multiple interlocking pieces are connected in a bent manner to form horizontal and vertical honeycomb interlocking assemblies of different lengths. Interlocking grooves are formed at the bends of adjacent interlocking pieces. The interlocking grooves on the horizontal honeycomb interlocking assembly are located below the length of the interlocking piece, and the interlocking grooves on the vertical honeycomb interlocking assembly are located above the length of the interlocking piece. Figure 7 As shown, horizontal and vertical honeycomb interlocking components of different lengths are interlocked vertically to form a honeycomb shape embedded in the honeycomb mold, which is a hexagonal honeycomb silicone mold.

[0052] S2. Slowly pour the carbon resin-based carbon nanotube solution into the gaps of the honeycomb mold, let it stand for 15 hours, and then demold to obtain the honeycomb core layer. Heat the adhesive film at 180°C for 30 minutes in a hot box and then cover the top and bottom panels respectively. Adhere the adhesive film to the top and bottom of the honeycomb core layer to obtain a fully composite hollow lattice-honeycomb hybrid sandwich structure.

[0053] Example 3

[0054] A fully composite hollow lattice-honeycomb hybrid sandwich structure is disclosed. The sandwich structure includes an upper panel, a lower panel, and a honeycomb core layer. The honeycomb core layer is formed by embedding honeycomb interlocking sheets into a honeycomb mold to form a lattice-reinforced fiber honeycomb reinforcement, which is then obtained by casting a resin-based carbon nanotube solution. The upper and lower panels are placed in parallel, and the honeycomb core layer is placed between the upper and lower panels to form a fully composite hollow lattice-honeycomb hybrid sandwich structure. The upper and lower panels are fiber composite boards.

[0055] The honeycomb interlocking assembly comprises multiple interlocking pieces, all of which are connected in a bent manner to form the honeycomb interlocking assembly, with the included angle of the bend being 120°. Interlocking grooves are formed at the bends of adjacent interlocking pieces, and the interlocking pieces are vertically interlocked through these grooves to form a honeycomb shape embedded in the honeycomb mold.

[0056] The locking plate is composed of 5 layers of fiber cloth, which are bonded together by an adhesive and IN2 guiding resin to form a prepreg. The prepreg is cut into pieces and locking grooves are made to form the locking plate. The locking plate has a height of 2mm and a length of 135mm.

[0057] The method for preparing the resin-based carbon nanotube solution includes the following steps:

[0058] IN2 epoxy flow-conducting resin and TX-10 emulsifier were placed in a beaker and mixed evenly. The amount of emulsifier was 11 wt% of the total amount of epoxy flow-conducting resin. The beaker was placed in a 40°C water bath and stirred at 500 r / min for 30 min until all bubbles were eliminated to obtain the resin matrix.

[0059] Weigh out carbon nanotubes and CR17 glass fibers, with the amount of carbon nanotubes being 0.6 wt% of the total epoxy resin and the amount of CR17 glass fibers being 0.6 wt% of the total epoxy resin. Add these two reinforcements to the resin matrix solution being stirred and continue stirring at 500 r / min for 30 min until the reinforcements and resin matrix are evenly mixed. Then add AT 30 curing agent, with the amount of AT 30 curing agent being 35 wt% of the total epoxy resin. Continue stirring the evenly mixed glass fiber / carbon nanotube reinforced resin matrix solution in a 40℃ water bath for 5 min to ensure the curing agent and resin matrix solution are fully mixed. Finally, place the fully mixed glass fiber / carbon nanotube reinforced resin matrix solution in a preheated vacuum drying oven for vacuum degassing treatment. The oven temperature is 80℃ and the vacuum degree is 10. -4 Pa yielded a resin-based carbon nanotube solution.

[0060] The above-mentioned method for preparing a fully composite hollow lattice-honeycomb hybrid sandwich structure includes the following steps:

[0061] S1. A prepreg is formed by bonding multiple layers of fiber cloth with resin. The prepreg is cut into pieces and interlocking grooves are made to form interlocking pieces. All the interlocking pieces are connected in a bent manner to form a honeycomb interlocking assembly piece. The included angle of the bend is 120°. Multiple interlocking pieces are connected in a bent manner to form horizontal and vertical honeycomb interlocking assemblies of different lengths. Interlocking grooves are made at the bends of adjacent interlocking pieces. The interlocking grooves on the horizontal honeycomb interlocking assembly piece are located below the length of the interlocking piece, and the interlocking grooves on the vertical honeycomb interlocking assembly piece are located above the length of the interlocking piece. Horizontal and vertical honeycomb interlocking assemblies of different lengths are interlocked vertically to form a honeycomb shape embedded in a honeycomb mold. The honeycomb mold is a hexagonal honeycomb silicone mold.

[0062] S2. Slowly pour the carbon resin-based carbon nanotube solution into the gaps of the honeycomb mold, let it stand for 24 hours, and then demold to obtain the honeycomb core layer. Heat the adhesive film at 180°C for 30 minutes in a hot box and then cover the top and bottom panels respectively. Adhere the adhesive film to the top and bottom of the honeycomb core layer to obtain a fully composite hollow lattice-honeycomb hybrid sandwich structure.

[0063] Impact performance testing was conducted on the hollow lattice-honeycomb hybrid sandwich structure prepared in Example 1 to test its impact resistance. The specific testing procedure was as follows: a drop hammer was used to conduct an impact vibration test on the hollow lattice-honeycomb hybrid sandwich structure. The test piece was fixed under the drop hammer to ensure that it would land on the test point when impacted. Different energies were used to conduct impact tests on the test piece, with impact energies of 16J and 20J, respectively. Multiple impact tests were conducted at different positions of the hollow lattice-honeycomb hybrid sandwich structure to prevent the randomness of the impact test from affecting the experimental results and thus affecting the accuracy of the experiment.

[0064] Figure 10 The impact performance diagram of the hollow lattice-honeycomb hybrid sandwich structure of Embodiment 1 of the present invention is shown below. Figure 10 As shown, the impact force on the honeycomb composite panel under an energy of 20J is as follows: when the impact contacts the top panel of the honeycomb composite panel, the honeycomb panel will generate the first peak force of about 2250N. At this time, the impact force breaks through the top panel and penetrates the top panel to reach the middle honeycomb layer. In the honeycomb layer, the energy of the projectile is gradually dissipated by the honeycomb layer. At about 8.5s, the energy is dissipated to 0, and the projectile stops moving.

[0065] Because impact tests are highly random and dependent on actual field operations, when the impact location is changed, Figure 11 This is an impact performance diagram of the hollow lattice-honeycomb hybrid sandwich structure in Embodiment 1 of the present invention when the impact position is changed, as shown in the diagram. Figure 11 As shown, the first peak value is mainly the impact force on the honeycomb panel when the projectile impacts the upper panel, which is about 2200N. When the projectile breaks the upper panel and impacts the honeycomb layer, the impact force it receives decreases. Then the projectile impacts the lower panel, at which point a second peak value appears. However, due to the energy loss of the projectile, the peak force is about 1600N. Subsequently, the projectile breaks the lower panel and penetrates the entire honeycomb sandwich panel.

[0066] The above experiments show that, compared with metal honeycomb (Wang Weifeng, Shi Weibing. Analysis of impact strength index of aluminum honeycomb sandwich panel, DOI:CNKI:SUN:JSTB.0.2020-01-137.), the present invention can withstand greater impact force under the same weight, proving that it has stronger impact resistance. By comparing with the literature, we can find that the hollow lattice-honeycomb hybrid sandwich structure of the present invention can reduce the structural weight without reducing its flushing performance. Therefore, this design has a very wide range of application prospects.

[0067] It should be noted that the connection relationships of components not specifically mentioned in this invention are all assumed to be based on existing technology. Since they do not involve the inventive point and are commonly used in existing technology, the structural connection relationships are not described in detail.

[0068] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

[0069] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A fully composite hollow lattice-honeycomb hybrid sandwich structure, characterized in that, The sandwich structure includes an upper panel, a lower panel, and a honeycomb core layer. The honeycomb core layer is composed of honeycomb interlocking sheets embedded in a honeycomb mold to form a lattice-reinforced fiber honeycomb reinforcement, which is then obtained by casting a resin-based carbon nanotube solution. The upper panel and the lower panel are placed in parallel, and the honeycomb core layer is placed between the upper panel and the lower panel to form a fully composite hollow lattice-honeycomb hybrid sandwich structure. The honeycomb interlocking assembly includes multiple interlocking pieces; The locking plate is composed of 3-8 layers of fiber cloth, which are bonded together by an adhesive to form a prepreg. The prepreg is cut into pieces and locking grooves are made to form the locking plate. The adhesive is IN2 flow-conducting resin. The method for preparing the resin-based carbon nanotube solution includes the following steps: The epoxy flow-conducting resin and emulsifier are mixed evenly and stirred in a water bath until all air bubbles are eliminated. Then, carbon nanotubes and fibers are added in sequence and stirred evenly. After adding the curing agent and mixing evenly, the mixture is heated and stirred in a water bath and vacuum degassing is performed to obtain a resin-based carbon nanotube solution.

2. The fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 1, characterized in that, All the locking plates are connected in a bent manner to form a honeycomb locking assembly, and the included angle of the bend is 120°.

3. The fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 2, characterized in that, The adjacent locking pieces are provided with locking grooves at their bends, and the locking pieces are vertically locked together through the locking grooves to form a honeycomb shape embedded in the honeycomb mold.

4. The fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 3, characterized in that, The height of the locking plate is 2mm and the length is 105-150mm.

5. The fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 4, characterized in that, The amount of emulsifier used is 9-11 wt% of the total amount of epoxy flow-conducting resin, the epoxy flow-conducting resin is IN2 epoxy flow-conducting resin, the emulsifier is TX-10 emulsifier, and the water bath temperature is 40℃.

6. The fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 5, characterized in that, The amount of carbon nanotubes used is 0.4-0.6 wt% of the total amount of epoxy conductive resin, and the amount of fiber used is 0.4-0.6 wt% of the total amount of epoxy conductive resin. The fiber is CR17 glass fiber.

7. The fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 6, characterized in that, The amount of curing agent used is 25-35 wt% of the total amount of epoxy superplastic resin. The curing agent is AT 30 curing agent. The vacuum degassing treatment temperature is 80℃ and the vacuum degree is 10. -4 Pa.

8. The method for preparing the fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 7, characterized in that, Includes the following steps: S1. A prepreg is made by bonding multiple layers of fiber cloth with resin. The prepreg is cut into pieces and interlocking grooves are opened to form interlocking pieces. All the interlocking pieces are connected in a bent manner to form a honeycomb interlocking assembly piece. The included angle of the bend is 120°. The interlocking pieces are interlocked in a vertical manner through the interlocking grooves to form a honeycomb shape embedded in the honeycomb mold. S2. Pour the resin-based carbon nanotube solution into the honeycomb mold. After filling the honeycomb mold, let it stand for 15-24 hours and then demold to obtain the honeycomb core layer. Adhere the upper panel and the lower panel to the upper and lower surfaces of the honeycomb core layer with adhesive film to obtain a fully composite hollow lattice-honeycomb hybrid sandwich structure.

9. The method for preparing the fully composite hollow lattice-honeycomb hybrid sandwich structure according to claim 8, characterized in that, The upper and lower panels are made of fiber composite boards.

Citation Information

Patent Citations

  • Honeycomb core board

    CN103112203A

  • Integrally-formed cellular three-dimensional fabric composite and preparation method thereof

    CN106739009A